Buprenorphine transdermal system compared with placebo reduces interference in functioning for chronic low back pain. Issue 1 (January 2015) - Yarlas, Aaron; Miller, Kate; Wen, Warren; Lynch, Shau Yu; Munera, Catherine; Pergolizzi, Joseph V.; Raffa, Robert; Ripa, Steven R.
Abstract: Objective : This study examines the efficacy of the buprenorphine transdermal system (BTDS) for reducing the interference of pain on physical and emotional functioning associated with chronic low back pain (CLBP). Methods : A post-hoc analysis used data from a randomized, placebo-controlled, double-blind trial of patients with moderate-to-severe CLBP. The Brief Pain Inventory (BPI) measured pain interference at screening, following a run-in period, and during the 12-week double-blind treatment phase. Statistical analyses examined treatment arm differences (BTDS vs placebo) for the following: BPI Interference subscale items and subscale scores at the trial end point (week 12); patterns of change in the Interference subscale scores over time; proportions of patients indicating mild or no interference following treatment; and proportions of patients showing improvement (30%, 50%, 2-point, or 4-point change in score from screening to week 12) for each item and subscale. Results : Mean scores for BPI Interference items and Interference subscale were significantly lower (ie, indicated less interference) for BTDS than for placebo (all P < 0.001). Treatment arm differences in Interference subscale scores emerged within 4 weeks of treatment. The BTDS patients were significantly more likely to indicate mild/no interference on 5 of 7 Interference subscale items following treatment ( P < 0.05). For most comparisons, BTDS patients were significantly more likely to show criterion-level improvements in Interference item and subscale scores ( P < 0.05 for differences). Discussion : Results indicate the efficacy of BTDS treatment, compared with placebo, for reducing the interference of pain on physical and emotional functioning in patients with moderate-to-severe CLBP. The advantage of BTDS was observed within 4 weeks of treatment, and was maintained throughout the 12-week treatment phase.